Assessment of genetic diversity and heterotic alignment of CIMMYT and IITA maize inbred lines adapted to sub-Saharan Africa - Gonhi, T.; Odong, T.L.; Dramadri, I.O.; Ochwo-Ssemakula, M.; Chiteka, Z.A.; Adjei, S.A.; Muungani, D.; Menkir, A.; Badu-Apraku, B.; Adejumobi, I.; Uwimana, B.; Dhliwayo, T.; et al. (Wiley, 2025)
Despite the breeding efforts by many institutions, maize (Zea mays L.) productivity in sub-Saharan Africa is still low. A limited number of productive maize hybrids have been developed partly due to a lack of knowledge on the diversity and heterotic relationship of the germplasm, especially in public breeding programs. Understanding the extent of diversity, structure, and heterotic grouping of available maize germplasm originating from different breeding programs is important to enhance long-term genetic gain in hybrid maize breeding programs by optimizing heterotic pools using modern breeding tools. Information about the genetic structure of the available germplasm could help breeders design effective breeding strategies to improve yield. This study was conducted to determine the genetic diversity, population structure, and heterotic alignment among 187 elite maize inbred lines from the IITA (International Institute of Tropical Agriculture) and CIMMYT (International Maize and Wheat Improvement Center) maize breeding programs. The inbred lines were genotyped with 9857 Diversity Array Technology sequencing based single nucleotide polymorphism markers. Hierarchical clustering revealed three major groups, with some subgroups consistent with the selection history, and pedigree of the inbred lines. Three broad groups were detected: two consisting of CIMMYT lines and a mixed group consisting of both CIMMYT and IITA inbred lines. The STRUCTURE analysis revealed six subpopulations (fixation index value = 0.58), which depicts a moderate genetic diversity among the materials. Population 2 comprises the highest number of genotypes (102) from both programs. More than 89% of the elite lines had homozygosity exceeding 95%, with the remaining lines requiring further inbreeding through repeated self-pollination. There was inconsistency in the predetermined heterotic groups' alignment between CIMMYT and IITA elite inbred lines. Analysis of molecular variance revealed that 96% of the total variation was accounted for by differences within groups, with the remaining 4% representing the variation between groups. This suggests that the two programs can benefit from germplasm exchange for the improvement of maize productivity.